The relationship between college counselor work responsibilities and burnout - Bohner, Gregory Lee (Kansas State University, 2018)
College counseling has been a unique profession among the helping professions that seeks to provide mental health and academic support to college students. One vocational danger for college counselors has been the onset of burnout. The loss of resources leading to burnout, as explained by the Conservation of Resources theory, may have been connected to today’s higher education administrative position of performing more responsibilities with less staffing. This research study examined the relationship between work duties assigned to college counselors, as measured by the College Counselor Activity Rating Scale, and the level of burnout for those counselors, as measured by the Shirom-Melamed Burnout Measure. The first five hypotheses examined the relationship between burnout and non-counseling duties by utilizing a hierarchical multiple regression analysis with various tests of mediation and moderation. The sixth hypothesis explored the assertion that college counselors at small institutions of higher education (institutional enrollment less than 5000 students) are more likely to engage in non-counseling duties. Members of the American College Counseling Association were recruited to serve as the population sample frame for the study. Because no instrument existed to measure counseling and non-counseling duties for college counselors, the College Counselor Activity Rating Scale was developed as a part of the study. Validation procedures were utilized in the form of an expert panel and pilot study for the College Counselor Activity Rating Scale. Of the six null hypotheses, all six were retained with limited power. Further analysis showed statistically significant relationships between burnout, perceived workload, and meaningful work. In addition, three non-counseling duties items, all related to administrative duties, were statistically significantly related to burnout. The key findings, implications and recommendations for future research were discussed.
Keywords: Burnout; College counseling; Meaningful work; Perceived workload; Non-counseling duties